Duration of cytopenias with concomitant venetoclax and azole antifungals in acute myeloid leukemia. Issue 14 (1st April 2021) - Rausch, Caitlin R.; DiNardo, Courtney D.; Maiti, Abhishek; Jammal, Nadya J.; Kadia, Tapan M.; Marx, Kayleigh R.; Borthakur, Gautam; Savoy, J. Michael; Pemmaraju, Naveen; DiPippo, Adam J.; Daver, Naval G.; Chew, Serena M.; et al.
Abstract : Background: Venetoclax (VEN) combined with the hypomethylating agent (HMA) azacitidine improves survival in patients aged ≥75 years with newly diagnosed acute myeloid leukemia (AML). VEN and HMA treatment can result in prolonged and often profound neutropenia, and this warrants antifungal prophylaxis. Azole antifungals inhibit cytochrome P450 3A4, the primary enzyme responsible for VEN metabolism; this results in VEN dose reductions for each concomitant antifungal. Limited clinical data exist on outcomes for patients treated with VEN, an HMA, and various azoles. Methods: The time to neutrophil recovery (absolute neutrophil count [ANC] > 1000 cells/mm 3 ) and platelet (PLT) recovery (PLT count > 100, 000 cells/mm 3 ) in 64 patients with newly diagnosed AML who achieved a response after course 1 of VEN plus an HMA were evaluated. HMA therapy included azacitidine (75 mg/m 2 intravenously/subcutaneously for 7 days) or decitabine (20 mg/m 2 intravenously for 5 or 10 days). Results: Forty‐seven patients (73%) received an azole: posaconazole (n = 17; 27%), voriconazole (n = 9; 14%), isavuconazole (n = 20; 31%), or fluconazole (n = 1; 2%). The median time to ANC recovery were similar for patients who did receive an azole (37 days; 95% confidence interval [CI], 34‐38 days) and patients who did not receive an azole (39 days; 95% CI, 30 days to not estimable; P = .8). The median time to PLT recovery was significantly longer for patients receiving azoles (28 vs 22 days; P = .01). The median times to ANC recovery (35 vs 38 days) and PLT recovery (26 vs 32 days) were similar with posaconazole and voriconazole. Conclusions: VEN plus an HMA resulted in neutropenia and thrombocytopenia, with the latter prolonged in patients receiving concomitant azoles. Concomitant posaconazole or voriconazole and VEN (100 mg) resulted in similar ANC and PLT recovery times, suggesting the safety of these dosage combinations during course 1. Abstract : Prophylaxis with azole antifungal agents during venetoclax and hypomethylating agent therapy affects the duration of thrombocytopenia but not neutropenia. The combination of 100 mg daily of venetoclax and either posaconazole or voriconazole results in similar durations of cytopenias.